Cat and mouse in a haunted house - Stilton,Geronimo (United States Of America Scholastic, Incorporated, 2004)
Lost in a dark, spooky forest! it was something that could only happen to me, Geronimo Stilton. Until I stumbled upon Curlypaw Cannycat's Castle.I quickly discovered the castle was haunted-by cats! Let me tell you, this is one case where curiosity almost killed the mouse.